Menumbuhkan Ide Usaha Bagi Ibu Rumah Tangga Untuk Mendukung Kemandirian Keuangan Keluarga - Nurmiati, Nurmiati; Murbayani, Murbayani; Ismail, Ismail; Lubis, Bastian (Patria Artha Journal of Community (PKM), 2025)
This Community Service activity aims to provide insight, motivation, and skills to the community in exploring and developing creative ideas as the first step in building independent businesses. Through counseling, interactive discussions, and hands-on practice, participants are encouraged to identify their potential in terms of skills, local resources, and market opportunities. This program is expected to encourage the community, especially housewives, to utilize business opportunities as a source of additional income, thereby achieving family financial independence. The results of the activity showed increase in participants' understanding and confidence in starting their entrepreneurial journey.